The Extract of Roots of Sophora flavescens Enhances the Recovery of Motor Function by Axonal Growth in Mice with a Spinal Cord Injury - Tanabe, Norio; Kuboyama, Tomoharu; Kazuma, Kohei; Konno, Katsuhiro; Tohda, Chihiro (Frontiers in Pharmacology, 2016)
Although axonal extension to reconstruct spinal tracts should be effective for restoring function after spinal cord injury (SCI), chondroitin sulfate proteoglycan (CSPG) levels increase at spinal cord lesion sites and inhibit axonal regrowth. In this study, we found that the water extract of roots of Sophora flavescens extended the axons of mouse cortical neurons, even on a CSPG-coated surface. Consecutive oral administrations of S. flavescens extract to SCI mice for 31 days increased the density of 5-HT-positive axons at the lesion site and improved the motor function. Further, the active constituents in the S. flavescens extract were identified. The water and alkaloid fractions of the S. flavescens extract each exhibited axonal extension activity in vitro. LC/MS analysis revealed that these fractions mainly contain matrine and/or oxymatrine, which are well-known major compounds in S. flavescens. Matrine and oxymatrine promoted axonal extension on the CSPG-coated surface. This study is the first to demonstrate that S. flavescens extract, matrine and oxymatrine enhance axonal growth in vitro, even on a CSPG-coated surface, and that S. flavescens extract improves motor function and increases axonal density in SCI mice.